Natural Lighting Design Strategies in Library of Mataram University - Alessandra Angelia Putri; Andika Citraningrum (Jurnal Mahasiswa Jurusan Arsitektur, 2019)
Reading room of a library serves as a place to accommodate reading activities. To fulfill its function, a good standard quality of natural lighting is needed. The standard of natural lighting in the library is 300 lux on the work plane, but the reading room in the library of Mataram University which is located in the city of Mataram still does not meet the standards. The research that uses DIALux v.4.13 software aims to find out the right natural lighting design strategies in order to improve lighting quality. The results showed that the change of furniture layout, addition of the opening dimensions, the addition of top lighting, the replacement of transparency values in lighting openings, then shading elements and material changes are added to existing imagery elements with high transparency values to increase the level of lighting at each point and spread light evenly in space.Keywords: Natural Lighting, Library, Design Strategy, Lighting Distribution